Effect of freezing on the quality of meat from broilers raised in different rearing systems - Giampietro-Ganeco, A. [UNESP]; Mello, J. L.M. [UNESP]; Souza, R. A. [UNESP]; Ferrari, F. B. [UNESP]; Machado, B. M. [UNESP]; Souza, P. A. [UNESP]; Borba, H. [UNESP] (CSIRO Publishing, 2017)
We evaluated the effect of freezing (-18°C) for 12 months on the qualitative characteristics of breast, thigh and drumstick meat. Samples from male Cobb 500 broilers raised in antibiotic-free (n = 125), conventional (n = 125) and organic (n = 125) rearing systems and samples from male Hubbard ISA broilers raised in a free-range (n = 125) rearing system were used. Among the studied systems, up to the ninth month of freezing, the organic chicken breast meat showed lower (P < 0.001) water activity (aw) (0.966, on average). After 12 months of freezing, samples of antibiotic-free and organic poultry showed a pH value similar to that of fresh meat (5.94 and 5.86, respectively). Freezing for 12 months preserved the redness of drumstick meat from conventional broilers (a∗ = 4.86, on average) and the rearing system did not influence the aw of drumstick meat during the entire experimental period. Freezing preserved the aw of conventional and organic chicken meat samples until the ninth month of evaluation (0.978 and 0.974, respectively). Lipid oxidation in the breast, thigh and drumstick samples from the four rearing systems increased (P < 0.001) from the third month of freezing onwards. There were variations in colour, pH, aw and lipid oxidation of chicken meat among birds raised in different rearing systems. Freezing chicken meat did not prevent colour and pH changes or occurrence of lipid oxidation and did not promote a reduction of aw to levels unfavourable to microbiological development.
Keywords: antibiotic-free; free-range; organic; shelf-life; storage.